Hepatitis B virus middle surface antigen loss promotes clinical variant persistence in mouse models. Issue 1 (31st December 2021) - Lin, Junyu; Li, Jing; Xie, Peilin; Han, Yue; Yu, Demin; Chen, Jia; Zhang, Xinxin
ABSTRACT: Hepatitis B virus (HBV) middle surface antigen (MHBs) mutation or deletion occurs in patients with chronic HBV infection. However, the functional role of MHBs in HBV infection is still an enigma. Here, we reported that 7.33% (11/150) isolates of CHB patients had MHBs start codon mutations compared with 0.00% (0/146) in acute hepatitis B (AHB) patients. Interestingly, MHBs loss accounted for 11.88% (126/1061) isolates from NCBI GenBank, compared with 0.09% (1/1061) and 0.00% (0/1061) for HBV large surface antigen (LHBs) loss and HBV small surface antigen (SHBs) loss, respectively. One persistent HBV clone of genotype B (B56, MHBs loss) from a CHB patient was hydrodynamically injected into BALB/c mice. B56 persisted for >70 weeks in BALB/c mice, whereas B56 with restored MHBs (B56 M+ ) was quickly cleared within 28 days. Serum cytokine assays demonstrated that CXCL1, CXCL2, IL-6 and IL-33 were significantly increased during rapid HBV clearance in B56 M+ mice. Furthermore, the enhancers and promoters of B56 were proved to be required for B56 persistence in mice. Ablating MHBs expression improved the persistence of a new clone (HBV1.3, genotype B) which was recreated by using enhancers and promoters of B56. These data demonstrated that MHBs deletion can promote the persistence of specific HBV variants in a hydrodynamic mouse model. MHBs re-expression restored a rapid clearance of HBV, which was accompanied by cytokine responses including the elevation of CXCL1, CXCL2, IL-6 and IL-33.